Principles and features to define and describe arts interventions for people with dementia: a qualitative realist study - Cousins, Emily; Tischler, Victoria; Garabedian, Claire; Dening, Tom (Taylor and Francis, 2018)
Background: There is currently no consensus regarding the definition and description of arts interventions for people with dementia. Developing a common language of classification will encourage reflection on artistic practice, support the evaluation and improvement of arts interventions, and enable their benefits to be communicated more effectively.